Antireflective array on zinc sulfide fabricated by femtosecond laser. (November 2022) - Zhang, Fan; Wang, Haoran; Yin, Kai; Duan, Ji'an
Highlights: Femtosecond laser Bessel beam micromachining fabricate antireflective microstructures. Fabry-Perot and Mie resonances in the multi-resonant surface work together to reduce reflection. The proposed method promots antireflective surfaces for wide civil and military applications. Abstract: Surface antireflection of zinc sulfide (ZnS) is crucial to improve the performance of infrared windows. In this study, femtosecond laser Bessel beam micromachining is proposed to fabricate antireflective microstructures (ARMs) on ZnS to suppress surface Fresnel reflection. The ARM consisting of approximately one hundred thousand holes within 30 × 30 mm 2 is uniformly spread on the ZnS surface. The Fabry-Perot (FP) and Mie resonances in the multi-resonant surface work together to reduce reflection and are enhanced with increasing ARM depth. The ARM depth is tunable by adjusting the pulse energy and is utilized to facilely regulate the reflectance spectra as well as wettability. Finally, the fabricated ARM with wide-angle antireflection and hydrophobicity proved the effectiveness of the proposed method.